Natural Resources of the Avondale Flora and Fauna Reserve Beverley, Western Australia - Lamont, Byron (1984)
The Avondale Flora and Fauna Reserve has an area just under 50 ha and is vested in the Western Australian Department of Agriculture. It forms a conspicuous ridge of granite overlooking the Avon Valley and rock outcrops are common. Its flora and fauna are representative of habitats now scarce in the wheat belt, but it is in a severely degraded condition. The vegetation is dominated by acacias rather than eucalypts. Twenty seven of the 159 plant species on the Reserve are weeds. A total of 276 animal species was collected or sighted, including a fox. Maps, photographs and commentaries are provided on the physiography, geology, major plant species distributions, vegetation, points of special interest and animal collection sites as a basis for future management and use of the Reserve. Management procedures will depend on what order of priority is given to the recreational, educational and conservation values of the site. The Reserve is in urgent need of weed control around the perimeter, and in the abandoned experimental plot and old pastures. Patch burning should be introduced in association with weed control.